Chuckie's ghost (New York : Simon Spotlight/Nickelodeon, 2005)
All the kids wear a costumes to school on Holloween except for Chuck, who is afraid that the new boy he met in the hallway is really ghost.
Keywords: Bashfulness -- Fiction; Fear -- Fiction; Halloween -- Fiction; Schools -- Fiction